Metabolite profile and in vitro cholinesterase inhibitory activity of extract and fractions of Aaptos suberitoides - Hanifa R. Putri; Rhesi Kristiana; I Wayan Mudianta; Edwin Setiawan; Aty Widyawaruyanti; Nitra Nuengchamnong; Nungruthai Suphrom; Suciati Suciati (GarVal Editorial Ltda., 2023)
Context: Marine sources such as sponges have shown a significant impact on the drug development from nature. Metabolites isolated from sponges show diversity in terms of structural features and pharmacological properties. Several sponges have been reported to have potency as cholinesterase inhibitors as one of the target therapies for Alzheimer's disease. Aims: To investigate the potency of marine sponge Aaptos suberitoides as cholinesterase inhibitors and to explore the chemistry of the sponge. Methods: The cholinesterase inhibitory assay was carried out against two enzymes, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), based on the modified Ellman's method. The chemistry of the active fractions was studied by LC-MS/MS method, followed by molecular networking using GNPS. Results: The results suggested that the extract and fractions inhibited both AChE and BChE enzymes. All samples demonstrated more potent inhibition against AChE compared to BChE enzymes. The n-hexane fraction gave the strongest inhibition against both AChE and BChE, with IC50 values of 4.76 µg/mL and 6.79 µg/mL, respectively. Based on the LC-MS/MS analysis, alkaloids were detected in the n-hexane and ethyl acetate fractions. Four alkaloids were identified in the ethyl acetate fraction, namely demethylaaptamine, aaptamine, isoaaptamine, and 8,9,9-trimethoxy-9H-benzo[de][1,6]naphthyridine at RT 1.52, 1.67, 2.92, and 3.22 mins, respectively. Aaptamine was also identified in the n-hexane fraction together with demethyloxyaaptamine. Conclusions: The extract, n-hexane, and ethyl acetate fractions of A. suberitoides have shown promising cholinesterase inhibitory properties against both AChE and BChE enzymes. The alkaloids present in the active fractions may be responsible for the bioactivity.